Evidence for presence of an arginine residue in the coenzyme A binding site of choline acetyltransferase. - Mautner, H G (1981)
Choline acetyltransferase (acetyl-CoA:choline O-acetyltransferase, EC 2.3.1.6) may be inactivated by arginine-specific reagents such as butanedione, phenylglyoxal, and camphorquinone-10-sulfonic acid. The enantiomers of the latter compound were prepared, but inactivation was not stereospecific. Protection against inactivation by the arginine-specific reagents was provided by CoA and, to a lesser extent, by 3'-dephospho-CoA. No protection was provided by choline, NAD+, NADH, NADP+, or NADPH. Sodium chloride could protect, to some extent, against inactivation by arginine-specific reagents; this protection showed no cation or anion specificity. The data are compatible with the postulate that the salt anion competes with the attachment of the 3'-phospho group of CoA to an active site arginine residue.